Estudo do potencial citotóxico de novos ésteres sintéticos derivados da mistura triterpenoidica α-/β-amirina em modelos experimentais in vitro - Meira, Assuero Silva (2011)
Triterpenoids are compounds that in recent years have aroused considerable interest because of their structural diversity and the discovery of a broad spectrum of pharmacological activities. This study evaluated the cytotoxic potential of four derivatives of a mixture of α-, β-amyrin in human tumor cell lines. Among these, only compound 3-O-α-Carboximaleinato of, β-amyrin (3a/3b) was active, especially in the leukemic cell line HL-60, with IC50 values ranging from 1.8 to 3.0 µM. This derivative had its cytotoxic evaluated, also at the other leukemia cell line, K562, with IC50 values ranging between 1.76 and 2.96 µM, suggesting a specificity of this substance for leukemia. And their specificity for tumor cells was confirmed in cytotoxicity assays in a strain of macrophages, J774 (IC50 between 3.10 and 3.60 µM) and mononuclear cells in human peripheral blood mononuclear cells, whose proliferation was not prevented, and there wasn’t damage in the DNA of these cells. None of the compounds showed hemolytic activity against erythrocytes of mice (EC50> 200 mg / mL), suggesting a cytotoxic mechanism more specific. Thus, to determine the mechanism of action involved, sequences of in vitro experiments were performed in HL-60 cell line. Cells were treated at different concentrations of the sample 3a/3b (1.5, 3.0 and 6.0 µM) during 24h. The viability of HL-60 cells (trypan blue test and flow cytometry) was reduced at concentrations of 3.0 and 6.0 µM after treatment. Morphological analysis of cellular changes performed by staining methods (May-Grünwald-Giemsa and acridine orange / ethidium bromide (LA / BE)) and by flow cytometry (membrane integrity) showed typical features of apoptotic cells (intact membrane , reduction of cell volume, picnotic nucleus and chromatolysis), also at concentrations of 3.0 and 6.0 µM. Further testing by flow cytometry revealed that there was externalization of phosphatidylserine, there was no formation of reactive oxygen species (ROS) and that the molecule 3a/3b only induced the extrinsic pathway of apoptosis by activation of initiator caspase 8 and subsequent activation of caspases 3 and 7. These data indicate a cytotoxic mechanism induced by an apoptotic pathway, involving death receptors. Therefore, these results indicate the cytotoxic potential of 3a/3b analogue.